2018
DOI: 10.1007/s00114-018-1539-z
|View full text |Cite
|
Sign up to set email alerts
|

Colour change in a structural ornament is related to individual quality, parasites and mating patterns in the blue tit

Abstract: Carry-over effects refer to processes that occur in one season and influence fitness in the following. In birds, two costly activities, namely reproduction and moult, are restricted to a small time window, and sometimes overlap. Thus, colour in newly moulted feathers is likely to be affected by the costs of reproduction. Using models of bird vision we investigated male colour change in a free-living population of blue tits (Cyanistes caeruleus) in three sampling occasions: spring 1, winter and spring 2. We rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 88 publications
4
15
0
Order By: Relevance
“…Here, we found that after season 1, males with more extra‐pair offspring increased their white cheek brightness, which has already been related to higher individual quality (Badás et al. ). The following season (season 2), males with brighter cheek feathers tended to gain paternity and sire more extra‐pair young.…”
Section: Discussionsupporting
confidence: 69%
See 4 more Smart Citations
“…Here, we found that after season 1, males with more extra‐pair offspring increased their white cheek brightness, which has already been related to higher individual quality (Badás et al. ). The following season (season 2), males with brighter cheek feathers tended to gain paternity and sire more extra‐pair young.…”
Section: Discussionsupporting
confidence: 69%
“…Achromatic contrasts confirmed that this color change between seasons could be perceived by avian vision (JND scores, available in Badás et al. ).…”
Section: Resultssupporting
confidence: 58%
See 3 more Smart Citations